2022
DOI: 10.1590/fst.42621
|View full text |Cite
|
Sign up to set email alerts
|

Use of bacterial cellulose as a fat replacer in emulsified meat products: review

Abstract: Emulsified meat products have a high fat content. The industry has been looking for strategies to replace fat with healthier products in order to meet consumer demands. This review aims to present studies on the use of BC as a substitute in emulsified meat products. In these studies, BC proved to be a potential fat replacer, as it maintained the same technological and sensory properties found in products with original fat content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 76 publications
(133 reference statements)
0
11
0
Order By: Relevance
“…In this case, it was found that, regardless of the fat concentration, the best results for adhesiveness are obtained with 2.34% BC, which represents tests 1 and 2. For Oliveira et al (2021), and according to Leonard et al (2019), the use of dietary fiber can influence the adhesiveness of the analyzed product. A study by Younis et al (2022) also highlighted this fact when using fructooligosaccharides (FOS), a dietary fiber, in meat products.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this case, it was found that, regardless of the fat concentration, the best results for adhesiveness are obtained with 2.34% BC, which represents tests 1 and 2. For Oliveira et al (2021), and according to Leonard et al (2019), the use of dietary fiber can influence the adhesiveness of the analyzed product. A study by Younis et al (2022) also highlighted this fact when using fructooligosaccharides (FOS), a dietary fiber, in meat products.…”
Section: Resultsmentioning
confidence: 99%
“…The aforementioned meat products are the main foods that contribute to the intake of saturated fats, which in turn are related to cardiovascular diseases. Hence these products are unhealthy (Oliveira et al, 2021;Öztürk-Kerimoglu et al, 2022;Ferro et al, 2021). To minimize these negative effects, several studies have been carried out aimed to reduce or replace some components used in the formulation of these products, such as, for example, fat reduction (Ferro et al, 2021), making them healthier (Sariçoban & Unal, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…BC is used for the synthesis of vegetarian meat, which is well-known as an analog for natural meat [ 129 , 130 ]. BC, in alliance with Monascus extract (which is obtained from a naturally occurring pigmented mould, Monascus purpureus ), has been used for the preparation of non-animal meat.…”
Section: Bc Applicationsmentioning
confidence: 99%